Case Studies in Multiple Sclerosis - Giacomini, Paul S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2017)
This handbook is a collection of clinical narratives that underscore the heterogeneous and unpredictable presentation of multiple sclerosis (MS) and give real-world clinical context to recent drug developments. This accessible and concise publication is intended to be used by a wide range of medical professionals, from specialist neurologists to medical trainees with an interest in neurology. An ideal clinical resource, Case Studies in Multiple Sclerosis provides an evidence-based discussion of each case, with an aim to enhance effective diagnosis and treatment of patients with MS and MS-related conditions.
1. Optic Neuritis. - 2. Myelitis -- 3. Disease-Modifying Therapies in MS -- 4. Management of Replaces with Corticosteroids -- 5. Breakthrough Disease -- 6. Progressive Multifocal Leukoencephalopathy -- 7. Induction Therapy -- 8. Diagnosing Primary Progressive Multiple Sclerosis -- 9. Symptomatic Care in Primary Progressive Multiple Sclerosis -- 10. Diagnosing Secondary Progressive Multiple Sclerosis -- 11. Walking Disability in MS -- 12. Cognitive Impairment in MS -- 13. Acute Disseminated Encephalomyelitis -- 14. Pediatric Multiple Sclerosis -- 15. Pediatric Multiple Sclerosis Mimics -- 16. Prenatal Planning with MS -- 17.MS Therapies and Pregnancy -- 18. Postpartum Issues with MS -- 19. Neuromyelitis Optica.
Keywords: Medicine; Neuroradiology; Neurology; Primary care (Medicine).; Medicine & Public Health; Neurology; Neuroradiology; Primary Care Medicine